AUTONOMES LERNEN IM DEUTSCHUNTERRICHT ALS FREMDSPRACHE - Babin-Rusu, Tatiana (Editura USM, 2024)
This article discusses the issue of pupil´s autonomy in foreign language teaching. Changes in modern society and in learning theory also require changes in language teaching, where the demand for learner autonomy becomes an integral part of the teaching-learning-assessment process. The concept of autonomy in learning has become important in language teaching discourse in recent decades. According to several authors, autonomy is described as an ability to take responsibility for one´s own learning.
Keywords: decision; pupil autonomy; learning purpose; self-guidance